99mTc-tilmanocept for lymphoscintigraphy. (2013) - Puleo, Christopher A; Berman, Claudia; Montilla-Soler, Jaime L; Zager, Jonathan S; Sondak, Vernon K
Vital blue dyes and radiolabeled colloids are widely used globally for intraoperative lymphatic mapping and sentinel lymph node biopsy. Until very recently, however, no radiolabeled agents were specifically approved for lymphoscintigraphy and none have been tested in prospective clinical trials. 99m Tc-tilmanocept was designed for use in lymphoscintigraphy and sentinel node biopsy, and has been evaluated in Phase II and Phase III clinical trials. In nonrandomized, prospective comparisons with vital blue dye, 99m Tc-tilmanocept reproducibly localized in regional lymph nodes after injection at the site of primary breast carcinomas and melanomas undergoing sentinel node biopsy, detecting nearly all visibly blue nodes and identifying more tumor-containing nodes overall, without missing any blue tumor-containing nodes. A Phase III trial in head and neck squamous cell carcinomas, with all patients undergoing complete node dissection after removal of the nodes detected with 99m Tc-tilmanocept, is currently underway. On 13 March 2013, the US FDA approved 99m Tc-tilmanocept (Lymphoseek) for use in lymphatic mapping procedures to assist in the localization of lymph nodes draining a primary tumor in patients with breast cancer or melanoma. Available evidence does not permit a definitive comparison with the other colloids that are commonly used for lymphoscintigraphy, but does suggest that 99m Tc-tilmanocept is an effective option with some potential, but as yet unproven, advantages.